EVALUASI KESUBURAN TANAH PADA LERENG BERBEDA DI PT. TANI PRIMA MAKMUR (PT. TPM) DESA ANGGOTOA KECAMATAN WAWOTOBI KABUPATEN KONAWE - Rustam, La Ode; Saputra, Afrisal; Syaf, Hasbullah (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
Soil fertility issues are a challenge in the development of the agricultural sector in Indonesia. The lack of initial information and evaluation of soil fertility status can lead to inappropriate decisions in land management, which in turn affects crop yields, which are usually low. Some fertilisation technologies also do not function optimally and do not show a good response. This study aims to identify the chemical characteristics of the soil and the level of soil fertility in the oil palm plantation of PT. Tani Prima Makmur (PT. TPM) in Anggotoa Village, Wawotobi District, Konawe Regency. The research location is the oil palm plantation of PT. TPM in Anggotoa Village, Wawotobi District, Konawe Regency, Southeast Sulawesi Province. This study was conducted using the free survey method (using the Toposekuen approach principle) to obtain differences in soil sampling locations. while on flatter slopes, soil fertility tends to be better. Several factors influencing fertility at this stage include Organic Carbon (OC), Base Saturation (BS), Cation Exchange Capacity (CEC), Total Phosphorus (TP), and Total Potassium (TP). Soil fertility status is classified as low on moderately steep slopes (15–25%) and moderate on flat slopes (0–8%) and gentle slopes (8–15%). Low organic matter content and base saturation are the primary factors affecting soil fertility in oil palm plantations.